Quantifying mechanisms of aeolian dust emission: field measurements at Etosha Pan, Namibia - Wiggs, G; Baddock, M; Thomas, D; Washington, R; Nield, J; Engelstaedter, S; Bryant, R; Eckardt, F; von Holdt, J; Kotting, S (American Geophysical Union, 2022)
Determining the controls on aeolian dust emissions from major sources is necessary for reliable quantification of atmospheric aerosol concentrations and fluxes. However, ground-based measurements of dust emissions at-source are rare and of generally short duration, failing to capture the annual cycle. Here, we provide new insights into dust dynamics by measuring aerosol concentrations and meteorological conditions for a full year (July 2015-June 2016) at Etosha Pan, Namibia, a globally significant dust source. Surface deployed field instrumentation provided 10- minute averaged data on meteorological conditions, aerosol concentration (mg/m3), and horizontal dust flux (g/m2 /min10). A Doppler LiDAR provided additional data for some of the period. 51 significant dust events were identified in response to strong E-ENE winds. We demonstrate that these events occurred throughout the year and were not restricted to the austral winter, as previously indicated by satellite observations. Peak horizontal flux occurred in the spring (November) due to strengthening erosive winds and highly desiccating conditions increasing surface erodibility. We identify a strong seasonal differentiation in the meteorological mechanisms controlling dust uplift; low-level jets (LLJ) on dry winter mornings (61% of all events), and cold pool outflows (CPO) in humid summer evenings (39% of events). Significantly, we demonstrate a very strong bias towards the contribution of low frequency and high magnitude events, with nearly 31% of annual horizontal dust flux generated by only 6 individual events. Our study demonstrates how longer-term (≈1 year), ground-based, and at source field measurements can radically improve interpretations of dust event dynamics and controls at major source locations.